Impact of Bullying-Victimization and Gender over Psychological Distress, Suicidal Ideation, and Family Functioning of Mexican Adolescents - Silvana Mabel Nuñez-Fadda; Remberto Castro-Castañeda; Esperanza Vargas-Jiménez; Gonzalo Musitu-Ochoa; Juan Evaristo Callejas-Jerónimo (MDPI AG, 2022)
Bullying victimization is strongly associated with increased psychological distress and suicide in adolescents and poor family functioning. Knowledge of gender differences influencing these factors will improve the prevention of mental problems and suicide in victimized adolescents. A total of 1685 Mexican secondary students, 12-17 years old (m = 13.65), of whom 54% were girls, responded to a standardized scale questionnaire to analyze such differences. Based on the statistical analysis, girls reported significantly lower family functioning and higher psychological distress and suicidal ideation than boys. The cluster analysis classified adolescents into high (5.78%), moderate (24.07%), and no-victimization (69.76%) groups. Boys predominated in the high (3.1%) and moderate-victimization (12.4%) clusters, and girls in the no-victimization group (39.51%). Multivariate statistical analyses found significant differences between the three groups, with the highest means of psychological distress and suicidal ideation and lowest family functioning in the high-victimization group. Only for suicidal ideation, there was an interaction between gender and the degree of victimization, with girls showing a higher increase of suicidal ideation than boys in the same cluster. Conclusions: Early detection and intervention in bullying-victimized adolescents, aiming to decrease psychological distress and suicidal ideation and strengthen family functioning, should consider contextual gender differences for effective prevention of mental health problems and suicide in adolescents.